Aplikasi Akademik Berbasis Web Mobile - Yowan Dwi Pebriani; Afriyudi (Teknik Komputer Politeknik Negeri Sriwijaya, 2022)
The processing of academic data is increasing day by day. In this case, school operators need an application that can support academic data processing and produce information needed by the school administration. There are two applications that mostly used by the school administrations. These two applications are word and excel. Unfortunately, word and excel didn't help a lot. The operation administrations still need to process the data academic manually. In 2014, the Ministry of Education and Culture of the Republic of Indonesia has finally issued an e-report application. This application is made for the needs of managing student report cards, biodata, grades, attendance and student transfer sheets, where the features are in accordance with the needs of the school. However, this application has a weakness. This application is too focused on report cards, thus forgetting the important role of the principal. In this application, features for principals such as teacher data information and student data information are less specific. As a result, when the principal needs more specific information, then the academic processing department will find it difficult to get the data information. To solve this problem, the researcher built an academic application using the prototype method. This method was used because it involves the users to participate in application development. The result of this study is a web-based academic application that has a mobile web feature, where there are new features for principals, teachers and students that are not available in the e-report application. Keywords— Academic Application, Prototype, Web Mobile